Implementation of a centralized health quarantine information system at the Pangkalpinang Port Health Office - Pratama, Fikry; Ahmad, Riris Andono; Sanjaya, Guardian Yoki (Universitas Gadjah Mada, 2022)
Purpose: This research aims to evaluate and analyze the factors affecting the implementation the health quarantine information system (SINKARKES) in KKP Pangkalpinang. Methods: Quantitative research with cross-sectional design research. The population studied several 65 respondents. Test statistical and data analysis using structural equation model Partial least-square with smartpls 3.0 software. Results: Five factors have significant effects in supporting the success of the implementation of SINKARKES, the quality of the system to the user satisfaction, the quality of information on user satisfaction, the quality of service to user satisfaction, the use of systems against net benefit and management support of net benefit. Conclusions: The implementation of SINKARKES uses a top-down approach with the development and adjustment of a system that runs thoroughly by focusing on meeting the needs of the central unit. This approach model is considered not ideal for the characteristics of the complex health quarantine information system module.